The effect of strontium doping on structural and morphological properties of ZnO nanofilms synthesized by ultrasonic spray pyrolysis method - Ouhaibi, A. (H. : ĐHQGHN, 2018)
Pristine and strontium doped ZnO nanometricfilms were successfully synthesized on heated glass substrates by the ultrasonic spray pyrolysis technique. The samples were characterized by means of X-ray diffraction (XRD), Atomic Force Microscope (AFM), UVevisible spectroscopy and photoluminescence (PL). X-ray diffraction patterns confirmed the hexagonal (wurtzite) structure, where the most pronounced (002) peak indicates the preferential orientation along the c-axis perpendicular to the sample surface. The intensity of this peak was increased rapidly from thefirst doping of 1% and its position was shifted toward higher angles under Sr-doping effect. For the used doping range of 1e5%, the Sr-doping at 3% attracted an especial attention. At this concentration, the particular transformation in the surface morphology of doped ZnOfilms was observed. The surface became granular and rough by expanding the crystallites' size. From optical measurements, transmittance and PL spectra were found to be sensitive to Sr-doping, where two different behaviors were observed before and after 3% of Sr-doping.